Synthesis, Structural and Luminescence Studies of Pyrochlore Phase Free TiO2:Dy3+ Produced by Solid‐state Reaction Method. Issue 6 (10th August 2016) - Kunti, Arup Kumar; Sekhar, Koppole Chandra; Pereira, Mario; Gomes, Maria Jesus Matos; Sharma, Shailendra Kumar
Abstract : TiO2 :Dy 3+ powders without any secondary phases have been prepared by solid‐state reaction through the optimization of synthesis conditions, doping amount and subsequently through a purification step. The maximum dysprosium solubility was found at 0.43 mol% in the range 800–900°C. The Rietveld refinement was performed to calculate the amount of phases and lattice constants. The effect of synthesis conditions and doping on strain and crystallite size is also discussed. Room temperature photoluminescence of TiO2 :Dy 3+ shows blue and yellow color emission. It is shown that yellow emission can be enhanced with the reduction of the pyrochlore phase Dy2 Ti2 O7 .